Determining the extent of heparan sulfate depolymerisation following heparin lyase treatment. (5th November 2016) - Carnachan, Susan M.; Bell, Tracey J.; Sims, Ian M.; Smith, Raymond A.A.; Nurcombe, Victor; Cool, Simon M.; Hinkley, Simon F.R.
Highlights: The extent of heparan sulfate enzyme depolymerisation has been investigated. Heparan sulfate oligomers are compared by SEC-RI and -UV. Composition analysis of several heparan sulfates are reported. Abstract: The depolymerisation of porcine mucosal heparan sulfate under the action of heparin lyases and analysis by size-exclusion chromatography (SEC) is described. Heparan sulfate treated to enzymic bond scission producing a Δ4, 5 double-bond and quantified by SEC with ultraviolet-visible (UV) spectroscopic detection (230 nm) indicated that the majority of the biopolymer (>85%) was reduced to disaccharides (degree of polymerisation (DP) = 2). However, analysis of the SEC eluant using refractive index (RI), which reflects the mass contribution of the oligosaccharides rather than the molar response of a UV chromophore, indicated that a considerable proportion of the digested HS, up to 43%, was present with DP >2. This was supported by a mass balance analysis. These results contradict the accepted literature where "complete digestion" is routinely reported. Herein we report on the composition and methodology utilised to ascertain the extent of depolymerization and disaccharide composition of this important biopolymer.